2009
DOI: 10.2478/v10042-008-0075-7
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of beta-enolase in normal and tumor rat cells.

Abstract: Enolase -a glycolytic enzyme is also expressed on the surface of eukaryotic cells such as macrophages, neutrophils, endothelial, neuronal, tumor cells. Surface enolase as plasminogen receptor plays an important role in myogenesis, tumorgenesis and angiogenesis. Determination of enolase localization in the cell lines may give rise to the elucidation of its receptor function in tumor cells. The cellular localization of the muscle-specific isoform of the enolase in normal rat cardiomyocytes (H9c2, an embryonic ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Similar observations were reported by Witkowska et al (2005) for a enolase-like protein of the surface bacterial cells of Klebsiella pneumonia. This phenomenon was observed in experiments with intact cell lines of rat sarcoma and normal cardiomyocytes (Seweryn et al, 2008).…”
Section: Resultsmentioning
confidence: 57%
“…Similar observations were reported by Witkowska et al (2005) for a enolase-like protein of the surface bacterial cells of Klebsiella pneumonia. This phenomenon was observed in experiments with intact cell lines of rat sarcoma and normal cardiomyocytes (Seweryn et al, 2008).…”
Section: Resultsmentioning
confidence: 57%
“…ENOB is a glycolytic enzyme, which can reversibly catalyze the conversion of 2-phosphoglycerate to phosphoenolpyruvate. This enzyme is found in muscle cells, where it may be involved in muscle development and regeneration ( 28 ). α-enolase (ENOA), another enolase, can switch to ENOB in rodents during muscle tissue development.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, enolase was revealed to be an important protein in many pathophysiological and disease processes (31). It is expressed on the surface of eukaryotic cells such as macrophages, neutrophils, endothelial, neuronal and tumor cells (32). Moreover, it is important in myogenesis, tumorgenesis and angiogenesis (32), as well as for pathogen invasiveness and the development of tumors (33).…”
Section: Discussionmentioning
confidence: 99%
“…It is expressed on the surface of eukaryotic cells such as macrophages, neutrophils, endothelial, neuronal and tumor cells (32). Moreover, it is important in myogenesis, tumorgenesis and angiogenesis (32), as well as for pathogen invasiveness and the development of tumors (33). It has been shown that enolase mediates the activation of enzymes involved in the invasion of tissues by pathogens and tumor cells, as well as in the evasion of host immune responses (34), and that it is sensitive to fluoride (35).…”
Section: Discussionmentioning
confidence: 99%